UTILIZATION OF FERMENTED SPINACH LEAVES (Amiranthus spinosus L.) IN FEED FORMULATION TO STIMULATE MOLTING OF MANGROVE CRAB (Scylla serrata) - Marniati Marniati; Salnida Yuniarti Lumbessy; Fariq Azhar (AQUASAINS, 2022)
There are several techniques that have been developed to accelerate the molting of mud crabs, namely ablation, mutilation and supplementation. One form of supplementation is through the use of fermented spinach leaves on mud crabs. This study aimed to analyze the use of fermented spinach (A. spinosus L) leaves in feed to stimulate the molting of mud crab (S. serrata). This research was conducted for 60 days. The experimental method used in a Completely Randomized Design (CRD) consisting of five treatments and three replications, namely trash fish (P1), Spinach Leaf Fermentation (FDB) 20% (P2), 25% (P3), 30% (P4), and 40% (P5). The results showed that the combination test feed of spinach leaf fermentation had a significant effect on absolute weight and length, specific growth rate (SGR), and feed utilization efficiency, but had no significant effect on feed conversion and survival. Treatment of feed with additional fermented of spinach leaf 30% gave a faster initial molting, which is in the first 10 days with a total of 6 molting crabs and a molting percentage of 40%. Feeding with the addition of 30% and 40% spinach leaf fermented concentrations can provide the best growth and feed efficiency for mangrove crabs.